The Effect of Emotional Intelligence, Organizational Climate, and Organizational Commitment on Employee Performance - Aulia, Anissa; Liana, Lie (Manunggal Halim Jaya, 2026)
Employee performance plays a vital role in determining organizational success. This study examines the influence of emotional intelligence, organizational climate, and organizational commitment on employee performance. The research population comprised 100 employees from Mega Baja Semarang and Bogor, Indonesia. One hundred questionnaires were distributed, and 92 valid responses were analyzed. Data were processed using SPSS 25. The findings reveal that emotional intelligence has no significant effect on employee performance, while organizational climate has a positive and significant effect. In contrast, organizational commitment shows no significant influence on employee performance. These results highlight the critical role of organizational climate in enhancing employee performance.